Stem Cells: Amazing Potential, Challenging Demand - Ramos García, Saditt (2015)
Stem cells application of stem cells raises a revolution in medicine beyond the preceding. This article describes basic information about them, shows the accepted stem cell therapies in clinical practice, mentions some of the amazing research being made for future clinical application in medicine and presents some warnings about unproven stem cell therapies. Finally, some information about confrontation between regulators and patients demanding accelerated authorization for unproven stem cell therapies.